You Are What (and Where) You Eat : Capturing Food Away from Home in Welfare Measures - Farfán, Gabriela (Elsevier, 2018)
Consumption of food away from home is rapidly growing across the developing world, and will continue to do so as GDP per person grows and food systems evolve. Surprisingly, the majority of household surveys have not kept up with its pace and still collect limited information on it. The implications for poverty and inequality measurement are far from clear, and the direction of the impact cannot be established a priori. This paper exploits rich data on food away from home collected as part of the National Household Survey in Peru, to shed light on the extent to which welfare measures differ depending on whether food away from home is accounted for or not. Peru is a relevant context, with the average Peruvian household spending over a quarter of their food budget on food away from home since 2010. The analysis indicates that failure to account for this consumption has important implications for poverty and inequality measures as well as the understanding of who the poor are. First, accounting for food away from home results in extreme poverty rates that are 18 percent higher and moderate poverty rates that are 16 percent lower. These results are also consistent, in fact more pronounced, with poverty gap and severity measures. Second, consumption inequality measured by the Gini coefficient decreases by 1.3 points when food away from home is included – a significant reduction. Finally, the inclusion of food away from home results in a reclassification of households across poor/non-poor status – 20 percent of the poor are different, resulting in small but significant differences in the profile of the poor in dimensions such as demographics, education, and labor market characteristics. Taken together, the results indicate that a serious rethinking of how to deal with the consumption of food away from home in measuring well-being is urgently needed to properly estimate and understand poverty around the world.